Effect of polymeric proanthocyanidin on the physicochemical and in vitro digestive properties of different starches. (August 2021) - Xu, Jiahui; Li, Xin; Chen, Jun; Dai, Taotao; Liu, Chengmei; Li, Ti
Abstract: The effect of polymeric proanthocyanidin (PPC, degree of polymerization was 8.61 ± 0.12) on the physicochemical and in vitro digestion properties of rice, potato and pea starch was investigated. Rapid viscosity analysis demonstrated that the peak, trough and final viscosity of rice and pea starch increased, but those of potato starch decreased when gelatinized with 5% PPC. Differential scanning calorimetry data showed PPC retarded the gelatinization of rice and potato starch and reduced the retrogradation enthalpy of three starches. In addition, PPC reduced the value of setback and the degree of retrogradation of rice starch to the greatest extent, followed by potato and pea starch, indicating that PPC restrained the short-term and long-term retrogradation of three starches. Fourier transform-infrared spectroscopy and X-ray diffraction results revealed PPC mainly altered the long-range ordered structure of starches through hydrogen bonding and hydrophobic interactions. Scanning electron microscopy micrographs showed that the starch-PPC pastes have looser and more stretched microstructures, further supporting the interaction between starch and PPC. Furthermore, the in vitro digestion results indicated that the digestibility of starch-PPC mixtures was lower than that of native starches. The results were beneficial to the extended application of functional proanthocyanidin in starchy food processing. Highlights: The digestibility of starch can be suppressed by polymeric proanthocyanidin (PPC). The pasting properties of three starches was changed after adding 5% PPC. PPC restrained short-term and long-term retrogradation of three starches. PPC altered long-range ordered structure of starch mainly through hydrogen bonding. PPC showed a greater effect on the digestibility of starch by co-gelatinization.